Big data analytics in forecasting voters’ sentiment vis-à-vis decision making in future general elections and by-elections in Malaysia post-2021 - Yasin, Megat Al Imran; Zukri Valenteno, M. A. (Global Academy Publishing House, 2023)
Barack Obama had practically won the 2012 US Presidential Elections on Big Data Analytics. While he was busy addressing a big rally in downtown Chicago or elsewhere, his teams were engaged in data mining on millions of American voters whom they believed to have the tendency to support their Democrat candidate against Republican Mitt Romney. If in the 2008 elections Obama was nicknamed The Social Media President, the Washington Post had in the 2012 US presidential re-elections dubbed him The Big Data President. Obama’s campaign has often been said to have revolutionised the American democracy, thus giving credence to his digital election campaign strategies, which were not only innovative but also effective. Such was innovation in today’s politics and elections, which is the subject of this paper. Big Data Analytics is all but new in Malaysian politics, rearing its infinitesimal presence only in the 2013 General Elections and then poised to become a game changer in the succeeding 14th General in Elections in 2018. However, the potential of big data analytics was not fully realised in local Malaysian politics as yet, and as much as it was in the Malaysian business sector which has been leveraging on data mining to push their products especially in the fast moving consumer goods (FMCG) segment. This paper shall discuss the prospective maximisation of big data analytics in the next general elections, possibly the GE15 and how it will tremendously effect the level playing field of political parties which were still wrapped in the age-old traditional-conventional method of predicting voters’ tendency and their voting pattern. As proven to be an effective political campaign tool for Obama and his presidential victory in 2012, Big Data Analytics should now be seen and anticipated as the inevitable for political parties in Malaysia to intelligently win the next general elections and by-elections.